Modification of the existing maximum residue levels and setting of import tolerances for trifloxystrobin in various crops - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal, 2025)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Bayer AG Crop Science Division submitted a request to the competent national authority in the Netherlands to modify the existing maximum residue levels (MRLs) for trifloxystrobin in table olives, olives for oil production, celeries, globe artichokes, leeks, herbal infusions from flowers, leaves and herbs and seed spices. In addition, a request was submitted to set an import tolerance in linseeds based on authorised use of trifloxystrobin in Canada. The data submitted in support of the request were found to be sufficient to derive MRL proposals for all the crops under assessment except for herbal infusion from flowers, leaves and herbs. Adequate analytical methods for enforcement are available to control the residues of trifloxystrobin on the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, European Food Safety Authority (EFSA) concluded that the short‐term and long‐term intake of residues resulting from the use of trifloxystrobin according to the reported agricultural practices is unlikely to present a risk to consumer health. The consumer risk assessment shall be regarded as indicative and affected by uncertainties.